2017
DOI: 10.3389/fmicb.2017.00062
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Whole Genome Sequencing of the First Case of Kosakonia radicincitans Causing a Human Bloodstream Infection

Abstract: The taxonomy of Enterobacter species is rapidly changing. Herein we report a bloodstream infection isolate originally identified as Enterobacter cloacae by Vitek2 methodology that we found to be Kosakonia radicincitans using genetic means. Comparative whole genome sequencing of our isolate and other published Kosakonia genomes revealed these organisms lack the AmpC β-lactamase present on the chromosome of Enterobacter sp. A fimbriae operon primarily found in Escherichia coli O157:H7 isolates was present in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Our baseline (T0) evaluations ( Figure 4 ) confirm recent publications arguing a decreased gut microbial alpha diversity in PCOS women compared to healthy controls [ 2 , 108 ]. These data also align with the common concept of a fast adapting diet-induced change of the microbiome [ 109 , 110 , 111 , 112 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our baseline (T0) evaluations ( Figure 4 ) confirm recent publications arguing a decreased gut microbial alpha diversity in PCOS women compared to healthy controls [ 2 , 108 ]. These data also align with the common concept of a fast adapting diet-induced change of the microbiome [ 109 , 110 , 111 , 112 ].…”
Section: Discussionsupporting
confidence: 87%
“…Polycystic ovary syndrome (PCOS) is one of the most prevalent endocrine and metabolic disorders in women, affecting 5–20% already from reproductive age worldwide, with phenotypes of various degrees of hyperandrogenism, anovulation and polycystic ovarian morphology [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study further demonstrates the utility of whole genome sequencing for pathogen identification in a clinical setting. Similarity, another report found that Vitek2 identified a blood culture derived isolate as E. cloacae but Illumina whole genome sequencing unequivocally determined it to be Kosakonia radicincitans (Bhatti et al, 2017 ). Further comprehensive work is therefore warranted to investigate clinical outcomes that result from these species misidentification.…”
Section: Discussionmentioning
confidence: 69%
“…In 2013, Enterobacter was divided into 5 new genera: Lelliottia, Pluralibacter, Kosakonia, epidemiological data on the occurrence of Kosakonia species in human samples. The first case of a human bloodstream infection with K. radicincitans was reported in a 61-year-old man with cholangiocarcinoma in Houston, TX, USA, in Dec. 2016 4 . Unfortunately, the authors of this report considered some common features of enteric bacteria to be virulence factors, and confused type IV secretion systems with type IV pili that are involved in several phenomena, not only pathogenicity 12 .…”
Section: Discussionmentioning
confidence: 99%